Critical care, critical gaps: assessment of burnout and behavioral profiles of ICU healthcare workers in China—a multicenter cross-sectional study - Chao Qing Zhang; Xing Li; Lei He; BinBin Xu; Yan Wu; Junjie He; Wei Wang; Zhong Qian Lu (Frontiers in Public Health)
BackgroundBurnout in intensive care unit (ICU) healthcare workers (HCWs) is a persistent threat to patient safety and workforce stability. While most evidence is derived from crisis settings, the behavioral determinants of burnout in routine, post-pandemic ICUs remain under-explored. This study applies a Knowledge-Attitude-Practice (KAP) framework to assess burnout-related KAP and identify its demographic, occupational, and institutional predictors.MethodsIn this cross-sectional study, 4,500 eligible ICU healthcare workers (HCWs) from 10 facilities in Yancheng, Jiangsu, China, were invited to complete a rigorously validated KAP survey; 3,342 responded (response rate = 74.3%), with KR-20 = 0.87 for Knowledge and Cronbach’s α ≥ 0.82 for Attitude and Practice. Descriptive statistics summarized participant characteristics, and multivariable logistic regression identified predictors of adequate (≥75%) KAP profiles.ResultsThe cohort was predominantly female (70%) and nurse-dominated (60%). Most respondents identified long shifts (84.0%) and heavy workloads (72.4%) as principal burnout drivers, yet only 35.9% were aware of formal prevention programs. Although 82.8% perceived burnout as a serious threat and 74.7% assumed personal responsibility, formal mitigation remained sparely 53.8% sought managerial support and 39.0% ever accessed counseling. Informal coping was pervasive: breaks (96.0%), peer discussion (78.9%), and exercise (76.8%). Access to workplace mental health resources was reported by 40.0%, with 50.0% reporting no access and 10.0% unsure, strongly predicting higher knowledge (adjusted OR 4.01, 95% CI 3.35–4.80) and good practice (OR 4.01, 95% CI 3.35–4.80). Clinical role, mid-career status, and 1–10 years’ ICU experience independently improved KAP scores (ORs 3.98–6.00, p < 0.001), whereas contract and temporary staff were consistently disadvantaged (OR 0.54, 95% CI 0.42–0.70). Gender, marital status, and ICU type were non-significant.ConclusionBurnout in ICU HCWs persists as a structural-behavioral challenge post-pandemic. Interventions should prioritize institutional support, equitable mental health access, and inclusion of vulnerable groups. This study shows the KAP model’s role in crafting scalable, data-driven prevention strategies for critical care.